The Primacy of Technology over Morality? Ethical and Legal Aspects of Surrogate Motherhood - Kobyliński, Andrzej (Studia Ecologiae et Bioethicae, 2017)
The main purpose of this article is to analyze the phenomenon of surrogate motherhood in the global dimension and to present the most important ethical and legal aspects of this medical procedure. In some countries, you can speak about the real industry of surrogacy. Only in India, we can find currently about 3,000 clinics offering this medical procedure. In the context of surrogate motherhood, we need first of all a new humanism, a new moral sensitivity, and appropriate legal regulations. It is necessary to create the international law, which will consider surrogacy as a form of modern slavery, of the commodification of human life, and the violation of human rights.